Healthy live births after mosaic blastocyst transfers with the use of next-generation sequencing - Yung-Liang Liu; Tzu-Ning Yu; Ching-Hui Chen; Peng-Hui Wang; Chi-Huang Chen; Chii-Ruey Tzeng (Elsevier, 2019)
Objective: To determine whether transfer of high-mosaicism (≥50%) embryos can result in healthy newborns. Case report: Two embryos resulting from controlled ovarian stimulation (COS) in Patient one, 41 years of age (y/o), underwent preimplantation genetic testing for aneuploidy (PGT-A), which demonstrated that one was mosaic (68%) and the other aneuploid; the mosaic embryo was transferred. Amniocentesis at 18 weeks of gestational age (GA) revealed a normal 46, XY karyotype. A phenotypically normal boy was delivered at 39 and 5/7 weeks of GA. For Patient two, 39 (y/o), nine embryos obtained after COS underwent PGT-A, indicating one euploid, four mosaic, and four aneuploid embryos. One euploid and one mosaic (50%) embryo were transferred, resulting in a twin pregnancy. Amniocentesis at 18 weeks of GA showed both fetuses had normal 46, XY karyotypes. Two phenotypically normal boys were delivered at 37 2/7 weeks of GA. Conclusion: Transfer of high-mosaicism embryos selected using current techniques can result in healthy euploid newborns. Amniocentesis suggested that mosaic embryos can be self-corrected before 18 weeks of GA. Keywords: Aneuploidy, Euploidy, Preimplantation genetic testing for aneuploidy, Mosaicism, Next-generation sequencing